Pengembangan lembar kegiatan siswa (LKS) berbasis penemuan terbimbing pada materi perbandingan trigonometri pada segitiga siku-siku kelas X SMA Islam - Nita Mahdiana; M. Shohibul Kahfi (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
The research was aimed to develop and to know the feasibility student’s worksheet based on guided discovery learning on trigonometric ratio on a right triangle for tenth grade of Islamic Senior High School Kepanjen. The development model oriented to the Plomp (2013) development model which consists of three stages: preliminary research, prototyping phase, assesment phase. The results showed that student’s worksheet was declared valid with a validity student’s worksheet was 3.21, the validity score of the student response questionnaire was 3.16, the validity score of observation sheet of student activities was 3.50 and the validity score of test was 3.33. The student worksheets also meet the practical criteria based on the results of students questionnaire with the practicability score that is 3.17 and observation sheet of student activities with the practicability score that is 3.78. The student’s worksheet developed also fulfills the effective criteria with a percentage of 81.81 percent of students getting a score above the KKM. Thus, the developed worksheet was feasible tu use because meets the criteria of valid, practical, and effective. Penelitian ini bertujuan untuk mengembangkan dan mengetahui kelayakan LKS berbasis penemuan terbimbing pada materi perbandingan trigonometri pada segitiga siku-siku kelas X SMA Islam Kepanjen. Model pengembangan mengacu pada model pengembangan Plomp (2013) yang terdiri dari 3 tahap: preliminary research, prototyping phase, dan assesment phase. Hasil penelitian menunjukkan bahwa LKS dinyatakan valid dengan skor kevalidan LKS 3,21, skor kevalidan angket respon siswa 3,16, skor kevalidan lembar observasi kegiatan siswa 3,50 dan skor kevalidan soal tes 3,33. LKS juga memenuhi kriteria praktis berdasarkan hasil angket respon siswa dengan skor kepraktisan 3,17 dan lembar observasi kegiatan siswa dengan skor kepraktisan 3,78. LKS yang dikembangkan juga memenuhi kriteria efektif dengan presentase 81,81 persen siswa mendapat nilai di atas KKM. Dengan demikian, LKS yang dikembangkan layak untuk digunakan karena memenuhi kriteria valid, praktis, dan efektif.